A qualitative investigation of the motivational climate in elite sport - Keegan, R. J.; Harwood, C. G.; Spray, C. M.; Lavallee, D. (Psychology of Sport and Exercise, 2014)
Objectives: This study examined the construction of the motivational climate surrounding elite sports performers by investigating the behaviours of coaches, peers and parents that were perceived to be motivationally relevant by elite athletes. Design: Qualitative - inductive. Method: Twenty-eight national, international and world-class athletes (15-29 years old) took part in semi-structured focus groups and interviews investigating how they believe coaches, parents, and peers influence their motivation. Results: An inductive content analysis indicated that elite athletes perceived a multitude of motivationally-relevant social cues. Coaches and peers were reported to be focal influences, whilst the role of parents appeared to be limited to emotional and moral support. Themes of feedback/evaluation, and pre-performance motivating behaviours were common to all social agents, whereas only the coach-athlete and peer-athlete relationships appeared to be important in moderating and directly influencing motivation towards sport. The influences of social agents related to the specific roles they performed in the athlete's life: instruction and leadership for coaches; emotional support, collaborative and/or competitive behaviours for peers, and for parents, a diminished role relative to when the athletes were younger. Conclusions: A central finding of the paper is that there was no discernible one-to-one correspondence between specific behaviours and their impact on motivation. Instead, the findings suggest complex contextual interactions between the immediate behaviours of social agents and the impact on the athlete's motivation. If supported, this finding would necessitate new and novel approaches in future research in order to facilitate a more advanced understanding of athlete motivation in elite sport.